FEATURES OF EDUCATIONAL PROCESS ORGANIZATION FOR SURGICAL DENTISTRY IN CONDITIONS OF EUROPEAN CREDIT-TRANSFER SYSTEM IMPLEMENTATION FOR DENTAL STUDENTS - Burega, Yu.O. (World of Medicine and Biology, 2015)
In connection with introduction of Bolognese training system it is necessary to optimize to contemporary demands the previous surgical dentistry training methods for students of dentistry. The ways of solving this problem are the improvement of student’s motivation during the training process by using the connection between studied discipline and dentist’s practice and development elements of clinical thinking as well as formation in students of Dentistry integral association of knowledge for surgical dentistry with different clinical causes in all patients age categories. For increasing of student’s interest proposed the ability of reception of additional points at the expense of unassisted training and the other kinds of student’s practice. For the improvement of student’s training in conditions of European Credit – Transfer System also proposed to result in correspondence to demands the integration of fundamental discipline with the course of surgical Dentistry that will help to enhance student’s motivation to study discipline. In addition, the fact that the major part of training program is assigned to unassisted studying of material leads to necessary to increase the number of used demonstrative material (dentistry phantoms, electronic atlases, photos, multimedia materials). In the structure of practical classes is necessary to include clinical and situational tasks that are directed not only for realization of current studies’ final control but also can allow students to use received fundamental knowledge in the future practical activity.